2015
DOI: 10.3390/molecules20011104
|View full text |Cite
|
Sign up to set email alerts
|

Novel Pyrazine Analogs of Chalcones: Synthesis and Evaluation of Their Antifungal and Antimycobacterial Activity

Abstract: Abstract:Infectious diseases, such as tuberculosis and invasive mycoses, represent serious health problems. As a part of our long-term efforts to find new agents for the treatment of these diseases, a new series of pyrazine analogs of chalcones bearing an isopropyl group in position 5 of the pyrazine ring was prepared. The structures of the compounds were corroborated by IR and NMR spectroscopy and their purity confirmed by elemental analysis. The susceptibility of eight fungal strains to the studied compounds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
33
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 46 publications
(59 reference statements)
5
33
0
Order By: Relevance
“…Notably, Compound 4 did not possess any significant cytotoxicity against the tested human cervical carcinoma cell lines, although it has the same functional group as hydroxamic acid derivatives, which have been proposed by Pal and Saha [ 8 ] as powerful anticancer molecules. Moreover, it has also been found that pyrazine and a 2-naphthol bearing glucoside have lost the activity even though pyrazine and its analogues have been reported for decades to possess broad spectrum biological activities [ 9 , 10 , 11 , 12 ]. Even 2-naphthol has been proved to be an efficient moiety for the design of antimicrobial agents [ 13 , 14 ].…”
Section: Resultsmentioning
confidence: 99%
“…Notably, Compound 4 did not possess any significant cytotoxicity against the tested human cervical carcinoma cell lines, although it has the same functional group as hydroxamic acid derivatives, which have been proposed by Pal and Saha [ 8 ] as powerful anticancer molecules. Moreover, it has also been found that pyrazine and a 2-naphthol bearing glucoside have lost the activity even though pyrazine and its analogues have been reported for decades to possess broad spectrum biological activities [ 9 , 10 , 11 , 12 ]. Even 2-naphthol has been proved to be an efficient moiety for the design of antimicrobial agents [ 13 , 14 ].…”
Section: Resultsmentioning
confidence: 99%
“…To the best of our knowledge, no antifungal activity has been described for MMV021013. Some studies have identified molecules with in vitro activity against mycotic and tuberculosis agents [33,34], as well as against protozoa and fungi [35]. These observations suggest that these pathogens may share common antimicrobial targets that may propel drug discovery against a broad range of infectious diseases.…”
Section: Discussionmentioning
confidence: 99%
“…The compound 1 was synthesized as per the protocol given elsewhere, and the purity of the compound was ascertained on the basis of elemental analysis and by comparing the melting point . The TLC analysis was carried out using benzene:ethyl acetate (7:3) as solvent system, and spots were visualized under UV or iodine chamber.…”
Section: Methodsmentioning
confidence: 99%